Leverage, Profitabilitas dan Peringkat Obligasi - Viola Desri Alisha; Febryandhie Ananda (Pusat Riset dan Inovasi Nasional, 2023)
Bond ratings are character symbols given by rating agencies to indicate the risk of a bond. This study aims to determine the effect of Leverage using debt to equity ratio (DER) calculations, Profitability using Return on Assets (ROA) calculations on Bond Ratings using calculations according to Bond Rating Interpretations in Financial Services Companies in the Banking Sector at PT. Pefindo for the 2017 – 2021 period used a purposive sampling technique to obtain 6 companies in a period of 5 years so that 30 samples were observed. The data analysis method used in this study is the panel data regression model. Based on the results of hypothesis testing, that Leverage has a negative effect and Profitability has no effect on Bond Ratings.